A modified anisotropic k-ω model for predicting flow and heat transfer in a rotating channel. (August 2018) - Niu, Yong; Zhang, Chuanjie; Xu, Guoqiang
Highlights: A modified anisotropic k - ω model taking account of turbulence pulsation was proposed. Results of the anisotropic model is in good agreement with the experimental data. The anisotropic k - ω model produced an inverse proportional function, Ro c ( Z/D ) = 1.5. The higher the TR, the earlier the location of the fluid separation appears. Abstract: A modified anisotropic k - ω model that takes into account turbulence pulsation was proposed. The model was then used to study the flow and heat transfer characteristics of a rotating channel. The study considered Reynolds numbers ranging from 3000 to 15, 000, rotation numbers from 0 to 1.31, and temperature ratios of 0.1, 0.17, and 0.22. The results obtained by the anisotropic k - ω model were compared with those obtained by the standard k - ω model. The anisotropic k - ω model was demonstrated to accurately predict the flow and heat transfer characteristics of the rotating channel and the results were in good agreement with the experimental data. By contrast, the standard k - ω model underestimated the heat transfer effect, especially for the trailing edge. Detailed flow analysis using the anisotropic k - ω model showed an inversely proportional relationship between the critical rotation number and the dimensionless distance. In addition, the study also found that the change of temperature ratio had an impact on the location of the fluid separation, the greater the temperature ratio, the earlier the fluid separation appears.